Management and treatment of a giant mandibular dentigerous cyst - Case report (Research, Society and Development, 2022)
Being classified as a developmental cyst, the dentigerous cyst (DC) is a benign pathology that arises from the accumulation of fluid in the space between the follicle surrounding the crown of an unerupted tooth. Its origin is uncertain and due to its classification, developmental lesions are not related to some type of inflammatory reaction as a cause. In most reports, DC is reported as asymptomatic, sometimes discovered on routine radiographs. The radiographic aspects of this pathology reveal a radiolucent, unilocular area with well-defined limits, surrounded by a sclerotic radiopaque halo, always in association with the crown of an impacted tooth. Type of treatment depends on pathology’s size, on patient’s age, and on which structures or teeth are involved, in addition to the patient's cooperation. The most common treatment is the total enucleation of the cyst along with the extraction of the impacted tooth. This article aims to present a report of a large dentigerous cyst in the mandible, in the posterior region of the right side associated with dental elements 48 and 47 in a 29-year-old male patient, caucasian, showing its clinical, imaging and histopathological properties and highlighting its form of treatment.